Selectivity of Benzyl Hydroxamic Acid in the Flotation of Ilmenite - Li, Lixia; Zhang, Chen; Yuan, Zhitao; Liu, Zhichao; Li, Chunfeng (Frontiers in Chemistry, 2019)
The decreased ground size of ilmenite-bearing ores challenges the selectivity of collectors of ilmenite. Taking advantage of flotation tests and density functional theory (DFT), the selectivity of benzyl hydroxamic acid (BHA) and the adsorption mechanism of oleate and BHA on ilmenite were systematically investigated. The flotation tests showed that BHA had good selectivity to ilmenite. In the DFT study, the favorable adsorption of BHA and oleate on the ilmenite surface were verified by the Mulliken population and the calculated interaction energies. Results indicated that the covalent bonds caused the adsorption of oleate on the ilmenite surface. The strong selectivity of BHA was due to abundant adsorption sites and solid adsorption of five-membered rings. The present investigation has important implications for further studies of BHA and will be helpful for screening and designing collectors for ilmenite flotation.